Water Absorption Behaviour and Mechanical Performance of Pineapple Leaf Fibre Reinforced Polylactic Acid Composites - Agung, E. H.; Mohamad Hamdan, Mohammad Hazim; Siregar, J. P.; Bachtiar, Dandi; Cionita, Tezara; Jamiluddin, Jaafar (Universiti Malaysia Pahang, 2018)
Fast-growing scientific work is focusing on alternative sources to replace modern synthetic fibre materials due to the adverse effects caused by petroleum-based materials. Natural fibre possesses high potential as a replacement for synthetic fibre and petroleum-based products. These materials are not only greener and environmental-friendly, but also safe for human health. As such, this study investigated the influence of compatibilising agent of maleated anhydride polyethylene (MAPE) on mechanical performance of pineapple leaf fibre (PALF) reinforced polylactic acid (PLA). The raw materials, such as PALF, PLA, and MAPE, were mixed by using a hot roller mixer machine and hot compression moulding at 190ºC. The specimens were then tested for water absorption and flexibility. The specimens were submerged in water for 0, 7, 14, and 21 days. Three types of tests were conducted, namely water absorption, tensile, and flexural assessments. The results of water absorption, tensile, and flexural tests for the untreated PALF composite (UPALF) and treated PLAF composite (TPALF) were recorded and explained. As a conclusion, composite materials based on hydrophilic natural fibre may reduce the tensile and flexural properties of the composite.